VISION AND MISSION ANALYSIS IN ISLAMIC EDUCATION STRATEGY MANAGEMENT: A CASE STUDY OF EDUCATIONAL INSTITUTIONS - Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; Ilzamudin; Ahmad Qurtubi; Agus Gunawan (Cakrawala Pedagogik, 2026)
This study aims to analyze the role of vision and mission in the strategic management of Islamic education and its implementation in educational institutions. Vision and mission are fundamental elements that serve as the direction and basis for policy formulation and strategic decision-making. This study used a qualitative approach with a case study method at an Islamic educational institution. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that vision and mission play a significant role in determining the direction of institutional development, improving management quality, and strengthening institutional identity. However, several obstacles remain in their implementation, such as a lack of stakeholder understanding, suboptimal socialization, and a mismatch between program planning and implementation. Therefore, a strengthening strategy is needed through internalization of the vision and mission values, increasing participation of all school members, and ongoing evaluation. The conclusion of this study confirms that the success of strategic management of Islamic education is greatly influenced by the clarity, consistency, and effective and sustainable implementation of the vision and mission.